Corporate debt booms, financial constraints, and the investment nexus - Albuquerque, Bruno (2021)
Does corporate debt overhang affect investment over the medium term? To uncover this association, I measure debt overhang with a concept of debt accumulation or debt boom, and combine leverage with liquid assets to capture financial constraints. Using a large US firm-level panel over 1985Q1-2019Q1, I find that debt overhang leads financially vulnerable firms to cut permanently back on investment: a 10 p.p. increase in the three-year change in the leverage ratio is associated with lower investment growth of 5 p.p. after five years compared to the most resilient firms. I also find that vulnerable firms experience weaker intangible capital growth in the aftermath of debt booms. Finally, I find that general equilibrium effects dominate, stressing the risk that firm-specific debt booms in a subset of firms may spill over to the rest of the economy.